2006
DOI: 10.1021/ja056745s
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer-Induced Conformational Changes and Melting In Designed Peptides in the Gas Phase

Abstract: The conformations of protonated RA15K, RA20K and RA15H (R = arginine, A = alanine, K = lysine, and H = histidine) have been examined in the gas phase as a function of temperature. These peptides were designed so that intramolecular proton transfer will trigger conformational changes between a helix (proton sequestered at the C-terminus) and globule (proton sequestered at the N-terminus). Kinetically controlled structural transitions occur below 400 K (from helix to globule for RA15H, and from globule to helix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
44
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 24 publications
10
44
0
1
Order By: Relevance
“…The Jarrold group has previously shown that the location of basic sites in polyalanine-based peptides has a profound impact on the gas-phase structures of the peptides, with helical structures being favored for peptides protonated at the C-terminus and globular structures being favored for peptides protonated at the N-terminus. 4, 6, 7, 56 The starting structure of monomeric melittin was taken from the protein data bank, entry 1MLT, and modified such that only three amino acids were positively charged. Because the C-terminus of melittin is naturally amidated and acidic residues are not present in the peptide, zwitterions were not considered.…”
Section: Resultsmentioning
confidence: 99%
“…The Jarrold group has previously shown that the location of basic sites in polyalanine-based peptides has a profound impact on the gas-phase structures of the peptides, with helical structures being favored for peptides protonated at the C-terminus and globular structures being favored for peptides protonated at the N-terminus. 4, 6, 7, 56 The starting structure of monomeric melittin was taken from the protein data bank, entry 1MLT, and modified such that only three amino acids were positively charged. Because the C-terminus of melittin is naturally amidated and acidic residues are not present in the peptide, zwitterions were not considered.…”
Section: Resultsmentioning
confidence: 99%
“…Gas-phase structures representing the different conformers types of [M+4H] 4+ ions filtered by the HAS-NEC model are shown in Supplementary Figure 8 It is worthwhile to mention that for the quadruply-charged ions, the elongation of the ion due to excessive charge density would not allow preservation of solution-like structures; therefore, these structures are discussed from a reference point of gas-phase structure stabilization. All three conformer types display a degree of helicity within the first peptide ion segment (Acetyl-PAAAAK) where the charge located at K(6) may stabilize the helix [44]. Significant coulomb repulsion and the presence of a positive charge at N-terminal locations of subsequent segments do not allow these portions to adopt specific secondary structure.…”
Section: Resultsmentioning
confidence: 99%
“…It may be argued that, for MDS simulations, one should consider the apparent gas phase acidities of different residues;[59, 60] however, estimating apparent gas phase acidities requires a knowledge of the distance between charge sites[59] which requires candidate structures from MDS. Even knowing the distance between potential charge sites may not be sufficient to accurately estimate correct locations as the most stable ion structure can dictate unique charge arrangements [61]. …”
Section: Resultsmentioning
confidence: 99%